HUBUNGAN ANTARA PERSEPSI ORANG TUA TENTANG PENDIDIKAN ANAK USIA DINI DENGAN MOTIVASI ORANG TUA MEMASUKKAN ANAKNYA KE TAMAN KANAK-KANAK DI KELURAHAN SUNGAI SALAK KECAMATAN TEMPULING INDRAGIRI HILIR - Suhna, Marsonia; Novianti, Ria; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the relationship of parental perception of early childhood education on the motivation of sending their children to kindergarten in Sungai Salak Tempuling District of Indragiri Hilir. The method used in this study is a quantitative correlation method. The population in this study were all parents who have children aged 4-5 years, amounting to 112 parents. Determination of the number of samples using probability sampling techniques as many as 52 parents. The data collection techniques used are questionnaire (questionnaire). Data were analyzed using analysis statistics person product moment correlation using SPSS Ver.20. The study hypothesis was a significant relationship between the perception of parents about early childhood education on the motivation of parents sending their children to kindergarten. It can be seen from the analysis of data obtained r = 0.390 and P = 0.004. Because p <0.05, it can be concluded that there is a significant relationship between the variables of perception with the motivation variable. So that means that Ho refused and Ha is received, and proved significant. Determinant coefficient value generated amounted KP = r2 x 100% = 15.21%, it can be seen that the perception of parents give the effect of 15.21% on the motivation of parents and the remaining 84.78% is determined by variables or other factors. Key Words: Perception, Motivation